Effect of ultrasonic treatment on the oral processing characteristics of Mianning ham - He, Jiaju; Wang, Wenli; Hao, Mai; Huang, Yue; CHen, Lin (Frontiers in Nutrition, 2024)
In this paper, the effect of ultrasonic treatment on the oral processing characteristics of Mianning ham was investigated. A sensory evaluation team of 10 evaluators with food professional background was involved in food mastication and dough collection. Oral processing analysis of ultrasonically treated hams was performed using particle distribution analysis, Headspace Solid-Phase Microextraction Gas Chromatography-Mass Spectrometry (SPME-GC-MS), electronic nose, and dynamic dominant sensory attribute testing. The results showed that compared with the control group, the chewing time and the number of chewing times of the ultrasonically treated hams during oral processing were significantly increased, the salivary content in the ham eating dough was significantly reduced, the types and contents of flavor substances were significantly increased, and the ultrasonic treatment significantly reduced the dominant organoleptic attributes such as saltiness and sourness of the Mianning hams. This paper takes Mianning ham bolus as the research object, analyzes the influence of ultrasonic treatment on the flavor perception of Mianning ham, and provides a theoretical basis for the optimization of ham back-end processing technology.